Anticonvulsant activity of alcoholic root extract of Cardiospermum halicacabum - Dhayabaran,Daniel (2012)
The aim of the present study was to evaluate the anticonvulsant effects of alcoholic root extract of Cardiospermum halicacabum L., Sapindaceae (ARECH), on the various murine models of epilepsy. The root extract of the plant was administered p.o. to male swiss albino mice at doses of 30, 100 and 300 mg/kg before evaluation. The brain monoamine levels were determined after two days administration. ARECH at doses of 100 and 300 mg/kg significantly delayed the onset of clonus and tonus in pentylenetetrazol, isoniazid and picrotoxin-induced convulsions. Tonic hind limb extension was also decreased at doses of 100 and 300 mg/kg as compared to vehicle control in maximal electroshock model. No significant motor toxicity was observed even at a highest dose administered, i.e. 900 mg/kg. Brain monoamine analysis by HPLC revealed a significant increase in GABAergic activity in C+ (in cerebellum) and C- (except cerebellum). These results suggested that ARECH possesses a significant anticonvulsant activity with a low motor toxicity profile. This activity may be attributed to an increase in GABAergic activity.